(3Yde GdeGdjI GdYGeI h GdJTQjY GdVQjHj Hjf GdfXQjI h GdJWHjb GdYdej (B/s - (3NUGhfI, LgGO SYjOs ((3YeGf(B: s (3OGQ hGFd ddfTQ hGdJhRjY(B, s, 2010)
(3GdeONd Gdi Yde GdeGdjI GdYGeI, JYQja hMLe h JbSje GdfabGJ GdYGeI h GdGKGQ GdGbJUGOjI dgG, GdGjQGOGJ GdYGeI, CedGc GdOhdI, GjQGOGJ GdOhdI ef GdQShe h ef GdVQGFH, GdbQhV GdYGeI, GdehGRfI GdYGeI, GdeHGOF GdYGeI aj GYOGO GdehGRfI GdYGeIs
(3HHdjhZQGajG(B: (3U(B.361s
Keywords: (3GdVQGFHs; (3GdVQGFH bhGfjf hJTQjYGJs; (3GdeGdjI GdYGeIs